Effects of tetrahydrouridine on pharmacokinetics and pharmacodynamics of oral decitabine - Lavelle, Donald (2012)
The deoxycytidine analog decitabine (DAC) can deplete DNA methyl-transferase 1 (DNMT1) and thereby modify cellular epigenetics, gene expression, and differentiation. However, a barrier to efficacious and accessible DNMT1-targeted therapy is cytidine deaminase, an enzyme highly expressed in the intestine and liver that rapidly metabolizes DAC into inactive uridine counterparts, severely limiting exposure time and oral bioavailability. In the present study, the effects of tetrahydrouridine (THU), a competitive inhibitor of cytidine deaminase, on the pharmacokinetics and pharmacodynamics of oral DAC were evaluated in mice and nonhuman primates. Oral administration of THU before oral DAC extended DAC absorption time and widened the concentration-time profile, increasing the exposure time for S-phase-specific depletion of DNMT1 without the high peak DAC levels that can cause DNA damage and cytotoxicity. THU also decreased interindividual variability in pharmacokinetics seen with DAC alone. One potential clinical application of DNMT1-targeted therapy is to increase fetal hemoglobin and treat hemoglobinopathy. Oral THU-DAC at a dose that would produce peak DAC concentrations of less than 0.2μM administered 2x/wk for 8 weeks to nonhuman primates was not myelotoxic, hypomethylated DNA in the γ-globin gene promoter, and produced large cumulative increases in fetal hemoglobin. Combining oral THU with oral DAC changes DAC pharmacology in a manner that may facilitate accessible noncytotoxic DNMT1-targeted therapy.